PHOTOINACTIVATION OF CANDIDA ALBICANS BIOFILM WITH GREEN LASER MEDIATED BY THE PAPAYA LEAF EXTRACT CHLOROPHYLL - Abdullah, Rismayani; Astuty, Sri Dewi; Armynah, Bidayatul; Tabaika, Pryandi M; Imelda, Imelda (Indonesian Physical Review, 2025)
This study aims to activate the effectiveness of Photodynamic Inactivation (PDI) as an antibacterial agent by using a green laser and papaya leaf chlorophyll extract to prevent Candida albicans cell death. Papaya leaf extract chlorophyll is known to have potential as a photosensitizer (PS) through its antimicrobial properties and ability to absorb optimal light photons at a wavelength range of 405–680 nm. Activation of chlorophyll molecules with appropriate light produces Reactive Oxygen Species (ROS), which are toxic to pathogenic microbes such as Candida albicans. The research method involves using PDI with a green laser light source and chlorophyll extract on Candida albicans biofilms. Four main treatment groups were applied, negative control (C-), positive controls with 10% (C1+) and 15% chlorophyll (C2+), irradiation for 60, 120, 180, 240, and 300 seconds (L1–L5), and combinations of irradiation with chlorophyll (L1F1–L5F2, where F1 for 10% chlorophyll and F2 for 15% chlorophyll), with measurements performed three times for each treatment. Living Candida albicans cells were detected using the XTT assay staining method. The results showed a significant decrease in activity in all treatment groups. Maximum activity was achieved in the L5F1 and L5F2 treatment groups with inactivation of 80% (p<0.05) and 83% (p<0.05), respectively. This study concludes that high papaya leaf extract chlorophyll concentrations combined with a green laser effectively inhibit Candida albicans biofilm.